Nephrology Consultation for Severe SGLT2 Inhibitor-Induced Ketoacidosis in Type 2 Diabetes: Case Report - Felice Nappi; Antonietta La Verde; Giovanni Carfora; Carlo Garofalo; Michele Provenzano; Ferdinando Carlo Sasso; Luca De Nicola (Medicina, 2019)
Euglycemic diabetic ketoacidosis (euDKA) related to sodium-glucose cotransporter 2 inhibitor (SGLT2-I), despite being reported as consistent, though infrequent, adverse effect in all trials on SGLT2-I in type 2 diabetes mellitus (T2D), still remains poorly known in the real world. On the other hand, the use of this new class of antihyperglycemic agents is expected to increase based on the recent solid evidence of remarkable cardiorenal protection. Therefore, improving awareness on risk factors, diagnosis, and treatment of euDKA is essential to allow correct implementation of SGLT2-I in clinical practice. We here report a T2D patient admitted to the emergency department and then transferred to the nephrology-dialysis unit because of severe euglycemic diabetic ketoacidosis (euDKA) related to sodium-glucose cotransporter 2 inhibitor (SGLT2-I). In our patient, a concurrent acute kidney injury at presentation, initially attributed to excessive use of nonsteroid anti-inflammatory agents, and the absence of severe hyperglycemia led to delayed diagnosis and proper therapy. The detailed description of decision-making process for diagnosis and therapy, and the analysis of precipitating factors as well, discloses the helpful contribution of nephrologist to optimize prevention and management of euDKA.